The road to Huddersfield : a journey to five continents - Morris, Jan. (New York : Pantheon Books, 1963)
This memoir by James Morris narrates stewardship at the World Bank including the untold story about the activities of the Bank across five continents.
ne 24/01/2019
Loans
Keywords: Economic development